2020
DOI: 10.1016/j.metop.2020.100035
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing the blood metabolome and genotype using long-range chromatin interactions

Abstract: Background —Maintenance of tight controls on circulating blood metabolites is crucial to normal, healthy tissue and organismal function. A number of single nucleotide polymorphisms (SNPs) have been associated with changes in the levels of blood metabolites. However, the impacts of the metabolite-associated SNPs are largely unknown because they fall within non-coding regions of the genome. Objective —We aimed to identify genes and tissues that are linked to changes in ci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Here we performed correlational analyses of experimentally derived data to identify eQTLs that physically connect Parkinson-SNPs to the genes that they control, in three dimensions, with the goal of understanding the putative functional impacts of known Parkinson-SNPs. 21 The integration of spatial and eQTL data allows for the identification of trans- eQTL–gene associations, 25 thereby nominating genes which have not previously been implicated in Parkinson’s disease. Our analysis identified 518 genes subject to regulation by 76 Parkinson-SNPs across 49 tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Here we performed correlational analyses of experimentally derived data to identify eQTLs that physically connect Parkinson-SNPs to the genes that they control, in three dimensions, with the goal of understanding the putative functional impacts of known Parkinson-SNPs. 21 The integration of spatial and eQTL data allows for the identification of trans- eQTL–gene associations, 25 thereby nominating genes which have not previously been implicated in Parkinson’s disease. Our analysis identified 518 genes subject to regulation by 76 Parkinson-SNPs across 49 tissues.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, computational prediction and text mining have been used to enrich experiments without inclusion in knowledgebases. In one study focused on finding associations across omic modalities, Fadason et al found interactions between metabolite-associated single nucleotide polymorphisms (SNPs), metabolites, and chromatin loops (i.e., physical contact between enhancers and promoters) in human blood by combining literature text mining, known drug interactions, Hi-C chromatin interactions, eQTL, and gene ontologies [279]. Additionally, computational predictions can be used to infer associations between analytes.…”
Section: Computationally Predicted Resourcesmentioning
confidence: 99%
“…Spatially constrained gene regulatory networks integrate chromatin interaction (Hi-C) data and eQTL analyses to associate variants with the genes they regulate. These networks represent one approach for assigning functions to da-SNPs ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%